Porphyromonas gingivalis triggers microglia activation and neurodegenerative processes through NOX4 - Magnusson, Anna; Wu, Rongrong; Demirel, Isak (Frontiers in Cellular and Infection Microbiology, 2024)
Periodontitis and infections with periodontal bacteria have been highlighted as risk factors for dementia. In recent years, attention has been drawn to the role of microglia cells in neurodegenerative diseases. However, there is limited knowledge of the influence of periodontal bacteria on microglia cells. The aim of the present study was to investigate the interactions between the periodontal bacteria Porphyromonas gingivalis and microglia cells and to unravel whether these interactions could contribute to the pathology of Alzheimer’s disease. We found, through microarray analysis, that stimulation of microglia cells with P. gingivalis resulted in the upregulation of several Alzheimer’s disease-associated genes, including NOX4. We also showed that P. gingivalis lipopolysaccharides (LPS) mediated reactive oxygen species (ROS) production and interleukin 6 (IL-6) and interleukin 8 (IL-8) induction via NOX4 in microglia. The viability of neurons was shown to be reduced by conditioned media from microglia cells stimulated with P. gingivalis LPS and the reduction was NOX4 dependent. The levels of total and phosphorylated tau in neurons were increased by conditioned media from microglia cells stimulated with P. gingivalis or LPS. This increase was NOX4-dependent. In summary, our findings provide us with a potential mechanistic explanation of how the periodontal pathogen P. gingivalis could trigger or exacerbate AD pathogenesis.